PARTISIPASI FORUM PEDULI JALAN RANGAU DALAM PERBAIKAN INFRASTRUKTUR JALAN RANGAU, KECAMATAN BATHIN SOLAPAN KABUPATEN BENGKALIS TAHUN 2022-2023 - ', Fauziah; Harirah, Zulfa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The phenomenon that occurs is seeing the participation of the Rangau Road Care Forum (FPJR). where the problem is due to vehicles passing repeatedly with loads that exceed the maximum limit of the vehicle itself, so that road user activities cannot run normally and have a direct impact on the surrounding community. Therefore, this research was conducted with the aim of finding out the participation of the Jalan Rangau Care Forum, Bathin Solapan District, Bengkalis Regency in 2022-2023. This study uses a qualitative method. The location of this research is in Buluh Manis Village and Farmer Village. Meanwhile, data collection techniques were carried out using interviews and documentation. Data analysis techniques by collecting data, reducing data, presenting data, and drawing conclusions. The results of this research are based on 4 stages of participation, namely participation in the planning stage of road infrastructure improvements including making decisions, both political and technical. Both participations in the implementation stage of this participation include how to mobilize existing resources, both funds and administrative activities. Third, participation in the receiving stage maintains and develops the results of road improvements, both in terms of quality and quantity, which can be seen from the percentage of success. And finally, participation in the stage of assessing road infrastructure improvements to what extent the implementation of improvements that have been carried out in previous stages, both active and passive, have been achieved. This can be seen based on concrete evidence of road improvements starting from collaboration with companies to successful bursama sittings and joint decision making, improvements to Rangau road infrastructure with commission IV of the Riau Province DPRD with the Riau Province PUPR service in the field of community development up to the stage of gradual road repair in 2022-2023. Keywords: Participation, road improvements.